The practice of system and network administration (Addison-Wesley, 2017)
Whether you use Linux, Unix, or Windows, this new edition describes th essential practices previously handed down only from mentor to protégé. This wonderfully lucid, often funny cornucopia of information introduces beginners to advanced frameworks valuable for their entire career, yet is structured to help even experts through difficult projects.